Choosing Schools, Choosing Safety: How Multiple Dimensions of Safety Shape School Choices - Chantal A. Hailey (AERA Open)
School choice programs have grown substantially over the past 30 years, enabling families to make school selections unbounded by their residential locations. While studies document families’ stated preferences for school safety, few quantitatively and comprehensively examine which safety components associate with families’ actual school choices. Leveraging New York City high school applications, I find that families factor multiple dimensions of safety into their school choices. Independent of schools’ academic, demographic, and geographic characteristics, families screen out schools with higher neighborhood and school violence and disorder; and metal detectors in the initial elimination phase of their decisions, and prefer schools in lower violence neighborhoods in the subsequent, more detailed decision-making phase. Families’ choices suggest variation in safety priorities by race and academic background. White, Asian, and higher-achieving students prioritize protection from neighborhood and school violence; Latine and Black students particularly prioritize lower school disorder; and White students ranked schools with metal detectors lower.